MAJELIS TABLIGH DALAM GERAKAN MEMAHAMI AL-QUR'AN DENGAN METODE MANHAJI - Adnan, M. Anas (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2014)
Consistent Allah said: "Fastbakoa good things," he called the Council Report "Muhammadiyah" Central Association invited the best all Mohammedans and Oedaoua heads, faculty and students to refer to the house of the Koran in Arabic, and the language of the Koran by our faith will never change as long as the heavens and the earth and deeds, and between the Council of simple to learn new ways that are easily affordable no doubt named "understanding of the methodology of modern Koran." And this method but rely image Note Quran same word, and translate words in Indonesian. And he was educated at the center Tfahim semantics in Part I, including from the real meaning and real, and can indicate whether there is reason for the decline of the verse, then acting in his analysis in Part II, Anatomy and grammar rules in Part III, then shows the meaning of rhetoric of passages in Part IV. And he stated that this new way - of course - the coolest way to teach the Quran Majid moment, and no doubt valid and worthy and decent education institutions and schools and education conducted by the Assembly at the state level, but also workshops and other Assembly every land, and no matter how educated.